2010
DOI: 10.1097/tp.0b013e3181e6f201
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Myocardium Regeneration With Skeletal Cell Sheets—A Preclinical Trial for Tissue-Engineered Regeneration Therapy

Abstract: SC sheet implantation improved cardiac function by attenuating the cardiac remodeling in the porcine ischemic myocardium, suggesting a promising strategy for myocardial regeneration therapy in the impaired myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 24 publications
(30 reference statements)
0
76
0
Order By: Relevance
“…In the Cell Processing Center of Terumo Corporation, skeletal myoblasts were isolated from the harvested skeletal muscle by enzymatic digestion in TrypLE Select TM (Thermo Fisher Scientific Inc, MA, USA) containing collagenase, expanded in culture in MCDB103 medium with fetal bovine serum for approximately 4 weeks, and cryopreserved. At least 7 weeks after the harvest of the skeletal muscle, the skeletal myoblasts were seeded at 6.0×10 7 cells per dish and incubated on temperature-responsive culture dishes (10 cm in diameter) to form a skeletal myoblast sheet (TCD-51073), as described previously. 7 Transplantation of TCD-51073 was performed through a left thoracotomy under general anesthesia, and 5 sheets of TCD-51073 (representing 3×10 8 cells) were transplanted onto a large area extending from the anterior wall to the lateral wall of the left ventricle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Cell Processing Center of Terumo Corporation, skeletal myoblasts were isolated from the harvested skeletal muscle by enzymatic digestion in TrypLE Select TM (Thermo Fisher Scientific Inc, MA, USA) containing collagenase, expanded in culture in MCDB103 medium with fetal bovine serum for approximately 4 weeks, and cryopreserved. At least 7 weeks after the harvest of the skeletal muscle, the skeletal myoblasts were seeded at 6.0×10 7 cells per dish and incubated on temperature-responsive culture dishes (10 cm in diameter) to form a skeletal myoblast sheet (TCD-51073), as described previously. 7 Transplantation of TCD-51073 was performed through a left thoracotomy under general anesthesia, and 5 sheets of TCD-51073 (representing 3×10 8 cells) were transplanted onto a large area extending from the anterior wall to the lateral wall of the left ventricle.…”
mentioning
confidence: 99%
“…At least 7 weeks after the harvest of the skeletal muscle, the skeletal myoblasts were seeded at 6.0×10 7 cells per dish and incubated on temperature-responsive culture dishes (10 cm in diameter) to form a skeletal myoblast sheet (TCD-51073), as described previously. 7 Transplantation of TCD-51073 was performed through a left thoracotomy under general anesthesia, and 5 sheets of TCD-51073 (representing 3×10 8 cells) were transplanted onto a large area extending from the anterior wall to the lateral wall of the left ventricle.…”
mentioning
confidence: 99%
“…Kondoh et al showed that the transplantation of skeletal myoblast sheets improved a cardiac performance and prolonged the life span of animals, associating with the reorganization of the cytoskeletal proteins of host cardiac tissue and the reduction of myocardial fibrosis, using a dilated cardiomyopathy hamster model [71]. The significant therapeutic effects by the transplantation of autologous skeletal myoblast sheets were also confirmed in large-animal modes (a pacing-induced canine dilated cardiomyopathy heart failure model and a porcine ischemic myocardium model) [72,73]. The transplantations of several adult stem cell sheets (adipose-derived and menstrual blood-derived mesenchymal stem cell sheets, and CSC sheets) also gave favorable therapeutic effects in small-animal models [41,74,75].…”
Section: Three-dimensional Tissues Fabricated By Using Autologous Celmentioning
confidence: 77%
“…In a pacing-induced canine dilated cardiomyopathy model, transplantation of skeletal myoblast grafts has shown improved cardiac function with reduction of fibrosis and apoptosis [17]. In a porcine cardiac infarction model, skeletal myoblast graft transplantation provided improvement of cardiac function with attenuation of cardiac remodeling [18]. Transplantation of skeletal myoblast grafts has also demonstrated that it is an appropriate and safe treatment for chronic myocardial infarction without increasing the risk of ventricular arrhythmias.…”
Section: Cell Sheet Transplantation In Preclinical and Clinical Studiesmentioning
confidence: 98%